Designing multicomponent nanosystems for rapid detection of circulating tumor cells - Banerjee, Shashwat S.; Khobragade, Vrushali; Khandare, Jayant J. (Methods in Molecular Biology, 2017)
Detection of circulating tumor cells (CTCs) in the blood circulation holds immense promise as it predicts the overall probability of patient survival. Therefore, CTC-based technologies are gaining prominence as a “liquid biopsy” for cancer diagnostics and prognostics. Here, we describe the design and synthesis of two distinct multicomponent magnetic nanosystems for rapid capture and detection of CTCs. The multifunctional Magneto-Dendrimeric Nano System (MDNS) composed of an anchoring dendrimer that is conjugated to multiple agents such as near infrared (NIR) fluorescent cyanine 5 NHS (Cy5), glutathione (GSH), transferrin (Tf), and iron oxide (Fe3O4) magnetic nanoparticle (MNP) for simultaneous tumor cell-specific affinity, multimodal high resolution confocal imaging, and cell isolation. The second nanosystem is a self-propelled microrocket that is composed of carbon nanotube (CNT), chemically conjugated with targeting ligand such as transferrin on the outer surface and Fe3O4 nanoparticles in the inner surface. The multicomponent nanosystems described here are highly efficient in targeting and isolating cancer cells thus benefiting early diagnosis and therapy of cancer.